2014
DOI: 10.1038/jp.2014.201
|View full text |Cite
|
Sign up to set email alerts
|

A national survey of obstetricians' attitudes toward and practice of periviable intervention

Abstract: OBs' willingness to intervene can impact periviable outcomes. These findings suggest that personal and institutional factors may influence obstetrical counseling and decision-making.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
19
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 18 publications
(19 citation statements)
references
References 20 publications
0
19
0
Order By: Relevance
“…The personal lower limit for certain treatment decisions associated with prematurity varied up to 4 weeks between individuals. It is known that personal preferences can influence counseling and decision-making [ 34 ]. For the interventions covered in the Dutch guideline, our results are fairly consistent with the guideline recommendations (transfer to a tertiary center at 23 +4/7 weeks GA and administration of corticosteroids at 23 +5/7 weeks GA).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The personal lower limit for certain treatment decisions associated with prematurity varied up to 4 weeks between individuals. It is known that personal preferences can influence counseling and decision-making [ 34 ]. For the interventions covered in the Dutch guideline, our results are fairly consistent with the guideline recommendations (transfer to a tertiary center at 23 +4/7 weeks GA and administration of corticosteroids at 23 +5/7 weeks GA).…”
Section: Discussionmentioning
confidence: 99%
“…Participants indicated 25 +0/7 weeks of GA as median lower limit, with a wide variation. Tucker Edmonds recently showed that obstetricians had a personal cutoff for performing a CS at a later GA (median 25 +0/7 weeks GA) than the institutional cutoff (median 24 +0/7 weeks GA) [ 34 ]. Having a neonatologist present at delivery and intubation after birth when necessary both showed a median lower limit at 24 +0/7 weeks of gestation, with relatively little variation; probably because these two items are seen as the minimum conditions that must be met when offering intensive care at 24 +0/7 weeks (and implicitly covered in our guideline).…”
Section: Discussionmentioning
confidence: 99%
“…Respondents reported institutional cutoffs of 23 weeks for resuscitation (34%) and 24 weeks for Cesarean sections (35%). At 23 weeks, two thirds ordered steroids, 43% recommended Cesarean section and 23% offered induction 12 . This lack of agreement is confirmed by a recent report 13 on practices and education surrounding anticipated periviable deliveries.…”
Section: Discussionmentioning
confidence: 99%
“…Our previous work has shown that nearly one third of generalists manage periviable deliveries without input from MFM consultants, which may especially be the case at 22 weeks. 21 Future studies should, however, include a larger MFM sample in order to capture the practices of the specialists with the greatest impact on periviable care. Furthermore, this study did not include neonatologists, whose responses may differ due to the availability of the online Neonatal Outcome Data, which may facilitate pediatric decision-making in this setting.…”
Section: Discussionmentioning
confidence: 99%